OBSERVASI DI SLBN ASUHAN KASIH KOTA KUPANG TERKAIT INTERAKSI SISWA DISABILITAS (TUNA GRAHITA/KETERBELAKANGAN MENTAL) DALAM PENGGUNAAN KOMPUTER - Januarius Funan; Marlia Delvina Barros; Siska Radja Hau; Diana Devanco Andre Moy; Diana Yanni Ariswati Fallo (FKIP Universitas Citra Bangsa, 2025)
This observation aims to describe the learning process, the use of technology, and the challenges faced by teachers in teaching children with special needs, particularly those with intellectual disabilities, in grades 5 and 6 at the Asuhan Kasih Special Needs School. Observations indicate that learning is still dominated by manual methods, with limited use of technology. Teachers demonstrate high dedication in adapting materials and activities to students' abilities.